ANALISIS PENGAMBILAN KEPUTUSAN PETANI MEMILIH VARIETAS BENIH PADI DI DESA TALOK KECAMATAN KALITIDU KABUPATEN BOJONEGORO - Aminudin, Ahmad; Diah Probowati, Deviana; Dawud, Moh Yusuf (Jurnal Sosiologi Pertanian dan Agribisnis, 2023)
Farmers' decision making on the use of rice seeds is one of the determining factors for achieving optimal results in a farming business, because if one chooses the type of rice seed, the results achieved are not optimal. This study aims to analyze what factors influence farmers' decisions on the use of rice seeds in Talok Village, Kalitidu District, Bojonegoro Regency. The sampling method in this study used the Random Sampling technique and to determine the sample size, the Slovin formula was used. Analysis of research data using the Multiple Linear Regression Analysis method with the help of SPSS 25 software. From the results of the study indicate that three variables that influence farmers' decisions on the use of rice seeds, namely the price of rice seeds, where to get the seeds, and promotion of 24.2% affect the product selection. rice seeds.